Blood platelets in the development of sepsis, septic shock and multiple organ failure syndrome - N. B. Serebryanaya; P. P. Yakutseni (Медицинская иммунология)
Participation of blood platelets in the development of sepsis is clearly illustrated by hemocoagulation disorders and frequently observed thrombocytopenia. In the patients with sepsis, thrombocytopenia develops rapidly, with minimal platelet counts registered on the fourth day of observation, after which the platelet counts usually rise. Continuous thrombocytopenia and absence of a relative increase in platelets are considered predictors of patient death. The mechanisms of thrombocytopenia developing in sepsis are quite diverse, but the processes in periphery are prevailing, e.g., the so-called “platelet consumption” which is determined by their activation, chemotaxis and isolation in the microvasculature. Recently, a mechanism has been identified for the accelerated removal of platelets with desialized surface glycoproteins from the circulation. Sialidases, also known as neuraminidases, are widely present in viruses and bacteria, and pharmacological inhibition of sialidases is able to withstand thrombocytopenia in the infectious process. The key role of platelets in the development of septic shock was revealed. Sequestration of platelets in the microvessels of the lungs and brain (manifesting as thrombocytopenia) is accompanied by rapid serotonin release, thus underlying the main clinical manifestations, e.g., decreased blood pressure, heart rate and increased capillary permeability. To counteract sharp release of this mediator, pharmacological attempts are made to inhibit the SERT transporter by means of selective serotonin reuptake inhibitors. Blood platelets are key participants in the pathogenesis of multiple organ failure syndromes, such as acute renal damage, acute respiratory distress syndrome, myocardial dysfunction, and sepsis-associated encephalopathy. To restore impaired vascular permeability in these conditions, in particular, sepsis-associated encephalopathy, a pharmacological S1P receptor mimetic is under study. The review specifies possible pathogenetically significant targets that can be used to perform pharmacological correction of conditions associated with sepsis and concomitant thrombocytopenia.